A Cytotoxic Activity of Clitoria ternatea Flower Tea with the Cinnamon and Lemongrass Oil Vapor against T47D Breast Cancer Cells - Cahyono, Edy; Handayani, Tri; WH, Nugrahaningsih; Azid, Saffanah Binti Mohd Ab; Alighiri, Dante; Zaky, Adrian Maulana; Aisyah, Sabila; Permatasari, Bella (Biosaintifika: Journal of Biology & Biology Education, 2024)
Breast cancer is a deadly disease for women. It is crucial to take preventive measures, one of which involves using natural ingredients as chemopreventive agents. Clitoria ternatea flowers, cinnamon, and lemongrass oil have been proven to have cytotoxic activity in several studies. This research aims to analyze the effect of adding cinnamon and lemongrass oil vapor to C. ternatea flower tea on the cytotoxic activity of T47D breast cancer cells. Cytotoxic activity testing was carried out colorimetrically using the MTT (3- (4,5-dimethylthiazol-2-yl) 2,5-diphenyl tetrazolium bromide) assay method. The results of the research showed that there was a decrease in the IC50 value of C. ternatea flower tea with the addition of cinnamon and lemongrass oil vapor. The IC50 value of C. ternatea flower tea without additional ingredients was the most potent with 14159 μg/mL, compared to 15 g addition of cinnamon with 1164 μg/mL; meanwhile, for 15 seconds of evaporation time for lemongrass, it was at 331 μg/mL, respectively This research shows the potential of C. ternatea flower tea with the addition of cinnamon and lemongrass oil vapor as a chemopreventive agent against breast cancer cells.